PEMANFAATAN KIRINYU (Chromolaena odorata) SEBAGAI SUMBER BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN WORTEL (Daucus carota ) - Murdaningsih Murdaningsih; Yosefa Sapo Mbu’u (BUANA SAINS, 2014)
The aim of this study was to determine the benefits of ‘kirinyu’ as a resource of organic matter and optimum quantities required in the growth and production of carrots. The study used a randomized block design with five treatments such as K0 (without kirinyu), K1 (kirinyu 5 ton/ha), K2 (kirinyu10 ton/ha), K3 K3 (Kirinyu 15 ton/ha),and K4 (Kirinyu 20 ton/ha). The variables measured were; plant height, total number of leaves, length of tubers, diameter of tubers and weight of fresh tubers per plant per plot and per ha. The results of this study indicate that the use of ‘kirinyu’ as a source of organic matter has a definite influence in the plant height in the ages of 4 MST, 8 MST, 10 MST, 12 MST, and total leaves in the ages of 6 MST, 8 MST. Also it influences the length of tubers, weight of tubers per plant per plot and per ha. It was determined that optimum growth of carrots; that is plant height (32.51 cm) total leaves (5.78 cm) length of tubers (10.71 cm) was attained with the use of 20 ton/ha weight of fresh tubers per plant (48.19 grams), per plot (7,93 kg) and total production of 21,09 ton per ha